Analysis of Connective Exocentric Phrases in the Soloraya.Solopos.Com News Article Title 'Boyolali Copper Businessman Killed Wednesday Night' - Esti Ningtyas; Yusni Khairul Amri (LingLit Journal Scientific Journal for Linguistics and Literature, 2024)
In Indonesian, the term phrase comes from English, namely phrase, which is sometimes called a phrase in Standard Indonesian Grammar. Various definitions of phrases show the important role of phrases in language. Exocentric phrases are combinations of words without containing the element "D" in them. Typically, these phrases consist of a noun combined with a conjunction, preposition, or some other word. Exocentric phrases are divided into three types, namely: 1) Directive exocentric phrases, 2) Non-directive exocentric phrases, and 3) Connective exocentric phrases. Connective exocentric phrases function to: 1) Show equality: Indicating that the elements being connected have an equal position in the sentence. 2) Connecting Ideas or Concepts: Connecting two or more related or conflicting ideas or concepts. 3) Simplify Sentences: Make sentences more concise by combining similar elements. By understanding connective exocentric phrases, language speakers can construct more complex and well-structured sentences.